Enhancing percutaneous kyphoplasty efficacy in elderly osteoporotic fractures through optimal cement filling ratio - Sun, Ningxue; Zhang, Yu; Xie, Deqian; Chen, Yating; Liu, Yang (Frontiers in Endocrinology, 2024)
Objective: To explore the appropriate bone cement filling ratio in percutaneous kyphoplasty (PKP) for the treatment of osteoporotic vertebral compression fractures (OVCF). Methods: Clinical and radiological data from 150 OVCF patients treated with PKP were retrospectively analyzed. Patients were categorized into three groups based on bone cement filling ratio: low (<0.4), medium (0.4-0.6), and high (>0.6) filling ratio groups. The clinical characteristics (age, gender, BMI, etc.) and related study data (bone cement leakage and its location, pre/post-operative Visual Analogue Scale (VAS), pre/post-operative Oswestry Disability Index (ODI), vertebral height restoration, kyphotic Cobb angle, etc.) among the three groups were compared using statistical software to compare to identify the most appropriate cement filling ratio. Results: The 0.4-0.6 group presented a lower cement leakage rate compared to the >0.6 group, and there were no significant differences in pre-operative VAS, post-operative day 2 VAS, post-operative month 1 VAS, and pre-operative ODI (p>0.05). However, significant differences were observed in post-operative month 3 VAS (p=0.002), post-operative day 2 ODI (p=0.002), post-operative month 1 ODI (p<0.001), and post-operative month 3 ODI (p<0.001). The "0.4-0.6" group showed better pain improvement and functional recovery compared with the ">0.6" group at the 3-month follow-up. While presenting the best vertebral height restoration, the “>0.6” group also exhibited the greatest variability. Additionally, no significant difference in Cobb angle changes was observed among the groups. Conclusion: A bone cement filling ratio of 0.4-0.6 in PKP treatment for OVCF strikes a favorable balance between complication reduction and positive patient outcomes, warranting it as an optimal filling volume.